Religious Identification, Switching, and Apostasy Among Protestants and Catholics in Northern Ireland: Individual and Cohort Dynamics Between Two Censuses 2001-2011 - Doebler, Stefanie (Journal for the scientific study of religion, 2018)
Religious identification has historically been salient in Northern Ireland as an ethnic-national identity marker. Thirteen years after the Good Friday Agreement that marked the start of the peace process in the country, the question arises whether religious affiliation in Northern Ireland has become less of an ethnonational identity marker and more of a personal choice. This article analyzes religious switching and apostasy between 2001 and 2011, using data from the Northern Ireland Longitudinal Study, a representative sample of approximately 28 percent of the population, linked to the 2001 and 2011 censuses. We found that the vast majority retained their self-reported religious affiliation, a tiny minority switched between Protestantism and Catholicism, and a significant minority, particularly among the young, switched to "none/not stated" or between Protestant denominations. Religious switching is associated with young age, higher education, and also socioeconomic deprivation. Experiences of social frustration appear to drive many to leave their faith.